Enhancing Information Literacy in Public Universities Through Policy Frameworks - Aviamu, Akwoyire Yaw; Ahenkorah-Marfo, Michael; Taylor, Joseph (Edulib, 2022)
Information literacy is evolving as a basic human right in the digital world, which promotes the social inclusion of all nations. The study sought to explore the role policies play in the delivery of information literacy in public university libraries. Using a semi-structured interview, the study sought to elicit the views of librarians in Ghana’s top-most universities on their knowledge about instructional services and availability of policy frameworks that guide the delivery of information literacy in academic libraries. It was revealed that different models of information literacy exist in academic libraries but librarians lacked a definite policy framework to prosecute the information literacy agenda. The study fills the gap in available literature on the role policy plays in information literacy, especially in developing countries. Universities and other higher educational institutions will find the results of this study useful in considering policies to guide the delivery of information literacy in their libraries.